Family-level Relationships of the Spittlebugs and Froghoppers (Hemiptera: Cicadomorpha: Cercopoidea) - J. R. Cryan; Svenson, G. J. (Systematic Entomology, 2010)
The spittlebug superfamily Cercopoidea (Hemiptera: Cicadomorpha) comprises approximately 3000 phytophagous species (including some economically important pests of grass crops) classified among the families Cercopidae, Aphrophoridae, Epipygidae, Clastopteridae and Machaerotidae. However, the monophyly of these taxa has never been tested and the evolutionary relationships among these major lineages are unknown. Presented here are the results of the first ever phylogenetic investigation of the higher-level relationships within Cercopoidea, based on DNA nucleotide sequence data from six loci (18S rDNA, 28S rDNA, histone 3, wingless, cytochrome oxidase I and cytochrome oxidase II) generated from exemplars of 109 spittlebug species representing all five described families, seven of eight subfamilies and 61 genera (eight additional exemplars, representing a selection of other Auchenorrhyncha taxa, were included as outgroups). The resulting topologies are used to evaluate the monophyly of each cercopoid family, and further to calculate divergence date estimates to examine the chronological origins and historical diversification of Cercopoidea. The results of this investigation suggest that: (i) four of the five described families are monophyletic; Epipygidae was recovered consistently as originating within Aphrophoridae; (ii) the exclusively Old World Machaerotidae is the most anciently diversified family of extant spittlebugs; (iii) New World Cercopidae (i.e. Ischnorhininae) constitute a derived monophyletic lineage; (iv) the genus Microsargane Fowler, classified currently within Aphrophoridae, actually belongs within Cercopidae; and (v) the origins of the major spittlebug lineages probably coincided with the breakup of Pangaea and, subsequently, Gondwana, as well as major floristic diversification such as the rise of angiosperms.
Keywords: Cercopoidea; Phylogenetics; phytophagous insects; spittlebug; taxonomy